Coronary artery calcium and cardiovascular risk factors analysis after radiotherapy for breast cancer (the CLARIFIER: a gender-based preventive medicine study) - Daniela Trabattoni; Maria Cristina Leonardi; Maria Elisabetta Mancini; Barbara A. Jereczek-Fossa; Barbara A. Jereczek-Fossa; Federica Cattani; Giulia Santagostino Baldi; Alice Bonomi; Arianna Galotta; Saima Mushtaq; Saima Mushtaq; Andrea Annoni; et al. (Frontiers in Cardiovascular Medicine)
IntroductionPatients receiving thoracic radiation (RT) are at increased risk for heart disease. Coronary artery calcium (CAC) is an independent risk factor for cardiac events.AimThe aim of this prospective, joint-institution, study was to analyze the relationship between cardiovascular risk factors (CVRF) known before breast cancer diagnosis and treatment, and the risk of developing coronary events in women undergoing adjuvant breast radiotherapy by measuring CAC.MethodsWomen (n = 92) diagnosed with early-stage breast cancer between 2010 and 2016 were enrolled and underwent cardiologic clinical assessment and coronary CT-scan for CAC score analysis, at least 5 years after RT.ResultsData obtained from 91/92 patients, showed a 36.2% incidence of pathologic Agatston CAC score, independent of the irradiated breast side. After grouping patients according to the total number of CVRF [group 1, n = 55 (60.4%): 0–2 CV risk factors; group 2, n = 36 (39.6%): 3–5 CV risk factors] significant differences were observed in CAC scores. Normal CAC scores (Agatston 0) were recorded in 70.9% in group 1 vs. 41.7% in group 2 (p = 0.005), while CAC-3 (Agatston ≥ 300) in 11.1% of group 2 only (p = 0.02), corresponding to clinical evidence of coronary disease. The risk of cardiac events was associated with increased age, early menopause, hypertension, high cholesterol levels, and smoking habits at the time of RT.ConclusionThis study helps to identify women at high-risk for cardiovascular events before RT and implement the best possible prevention of late post cancer treatment events. Clinical Trial RegistrationClinicalTrials.gov, Identifier (NCT05775822).